Emerging colistin resistance in Salmonella enterica serovar Newport isolates from human infections. Issue 1 (1st January 2020) - Elbediwi, Mohammed; Pan, Hang; Biswas, Silpak; Li, Yan; Yue, Min
ABSTRACT: Worldwide emergence of Salmonella enterica serovar Newport ( S . Newport) infection in humans, in parallel with a significant increasing prevalence of antimicrobial resistance (AR), is a serious public health concern. However, the prevalence of S . Newport resistance in China remains largely unknown. A retrospective study of 287 S. Newport clinical isolates collected during 1997–2018 was undertaken for characterization of AR profiles using the micro-dilution assay. We found a recent emergence of colistin resistance in four Chinese clinical isolates, including mcr -1-positive isolates. Importantly, phylogenomic and microbiological investigations indicate multiple independent clonal transmission of colistin-resistant S. Newport isolates of different seafood origins. Our study highlights potential reservoirs for transmission of colistin resistance and suggests that the global food supply chain may facilitate this dissemination.